Smoking behaviour can be predicted by neighbourhood deprivation measures. (December 1995) - Kleinschmidt, I; Hills, M; Elliott, P
Abstract : STUDY OBJECTIVE--To assess whether small area measures of socioeconomic deprivation predict variation in individual smoking behaviour. To examine the adequacy of an individual level statistical model for the analysis of data on groups of individuals who live in the same geographical area. DESIGN--Individual level and two level logistic regression analysis of data on individual smoking from a regional health survey, and neighbourhood deprivation scores for 1991 census wards calculated from 1991 census data. SETTING--The North West Thames Regional Health Authority area. PARTICIPANTS--Random sample of 8, 251 adults in North West Thames Regions. MAIN RESULTS--There was a highly significant association between being a smoker and the neighbourhood deprivation score of the area of residence. With the two level model, after allowing for age and sex, the estimated odds ratio of being a smoker for an individual in the highest quintile of deprivation compared with someone in the lowest quintile was 1.52 (95% confidence interval 1.33, 1.74). Results obtained using the individual level model were similar. Variation between wards accounted for around 6% of the total variation in smoking behaviour after neighbourhood deprivation of the ward had been taken into account. Deprivation of the area of residence remained a significant predictor of smoking status even after the socioeconomic group of the individual has been taken into account. CONCLUSIONS--Neighbourhood deprivation of the area of residence is a predictor of smoking status of individuals. In this example the two level model was reasonably well approximated by the individual level model.